Religious Beliefs among the Oromo: Waaqeffannaa, Christianity and Islam in the Context of Ethnic Identity, Citizenship and Integration - Ta’a, Tesema (Ethiopian Journal of the Social Sciences and Humanities, 2023)
The Oromo are the largest single ethnic group speaking Cushitic language and inhabiting the Oromia Region of Ethiopia. The annals of the Oromo reveal that the Oromo religion was neither Christianity nor Islam but was an indigenous religion known as Waaqeffanna. The Oromo Waaqa is similar to the God of the Christians and Allah of the Muslims. The Oromo never substitute other gods or curved statues for their Waaqa. Belief in one supernatural power is therefore a common denominator for the Oromo and other peoples which could be an important asset for democratization creating harmony, understanding and better integration among the population. The Waaqeffanna practice among the Oromo is closely linked with the Gadaa institution. Using the challenging paradigm established by Bartels in his work on Oromo Religion, this paper discusses continuity and change in the Oromo religious beliefs and the tolerance they have developed examining the impact of Christianity and Islam on Waaqeffanna in general and that of Islam in particular. Whether the Oromo have become Christians or Muslims, however, a true belief in one God (Waaqeffanna dhugaa) remains the basic tenet of Oromo identity. A remark will also be made on the extent to which religious freedom enshrined in the country’s constitution is respected for all citizens. Conflicting identities among themselves and the state’s intervention in religious affairs are very likely to hamper peaceful co-existence, democracy and integration. The paper attempts to show the historical symbiotic relationship between Waaqeffana and the major religions reflecting a significant degree of tolerance on the part of the former. Based on the historical accounts at our disposal we will finally underscore the need for more religious tolerance among the Ethiopian peoples as one of the indispensable factors for effective population integration, genuine democracy and peaceful co-existence.